GEOTHERMAL RESERVOIR MODELING BY USING POLYGON TALWANI 2-D METHOD - PRAYANTA PANDIA (NIM : 90213005), SUKA
The aim of this study is to model the geothermal reservoir using two-dimensional polygons Talwani. Geothermal energy is one alternative energy to meet human needs for energy. Generally, geothermal energy is used to turn a generator to produce electricity. In this study, the heat reservoir is a fluid assumed mass density 1000 kg / m3. To find the location of the reservoir, then used some exploration methods, one of which is the gravity method. Gravity method uses the principle of gravity between the masses, so that different mass meeting will provide acceleration values measured are different. The final value is sought in this method is the Bouguer anomaly, which is the result of the measurement values are then carried out a correction - a correction. In interpreting the object cause of the anomaly, then in this study used a polygon method Talwani. This method assumes that the heat reservoir can be considered as objects berbanyak side. The programming used in this study is C ++ as the language quickly in command execution.